Service Communication On Unisba Student Satisfaction During The Covid-19 Pandemic - Tresna Wiwitan; Mohammad Subur Drajat; Nurrahmawati Nurrahmawati (MediaTor (Jurnal Komunikasi), 2021)
One of the indicators of stakeholder assessment of higher education institutions is the service factor provided by the institution.  Online lectures and lecturer services – educators to students – are part of the communication services that Unisba provides to its students. Student dissatisfaction with the services that faculties and universities provide is usually conveyed on social media and it can be a boomerang effect for Unisba. Customer Relationship Management (CRM) is a form of service communication that is based on building relationships with customers.  The purpose of this study was to determine and analyze the effect of service communication on student satisfaction. This study uses quantitative analysis method to test the influences. The population is Unisba strata-1 (S1) active students in the 2020/2021 academic year, totaling 12,854 students.  To determine the sample size, the authors used the Slovin formula with a margin of error of 0.09 and the number of samples is 132 students.  The sampling technique that the authors used was the stratified probability one. The data analysis that we used was simple linear regression to see the influence of people, process, and technology aspects on Unisba student satisfaction.  The research results show that human, process, and information technology aspects have a significant influence on Unisba student satisfaction.